2018
DOI: 10.1144/sp477.23
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the effect of mass-transport deposits on fault propagation in Penobscot area, offshore Nova Scotia

Abstract: Three-dimensional (3D) seismic data and well logs from the Penobscot area, located within the Scotian Basin offshore Nova Scotia, are used to assess the role of mass-transport deposits (MTDs) on fault propagation. Four MTDs characterized by chaotic seismic facies were mapped, with the earliest hosted by the Late Cretaceous–Recent Dawson Canyon Formation and latest three hosted by the Banquereau Formation. Two types of faults were also mapped. R-faults are regional faults that cut across all the interpreted MTD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Given that MTDs are ubiquitous in sedimentary basins, various authors have shown that they can be used as structural markers by constraining the timing of fault growth and MTD emplacement (e.g. Omosanya & Alves 2014, and references cited within Omeru et al 2018). The research team tests this method to determine if MTDs can be used as markers for fault propagation on four MTDs within the Scotian Basin.…”
Section: Tectonics and Mass Movementsmentioning
confidence: 99%
“…Given that MTDs are ubiquitous in sedimentary basins, various authors have shown that they can be used as structural markers by constraining the timing of fault growth and MTD emplacement (e.g. Omosanya & Alves 2014, and references cited within Omeru et al 2018). The research team tests this method to determine if MTDs can be used as markers for fault propagation on four MTDs within the Scotian Basin.…”
Section: Tectonics and Mass Movementsmentioning
confidence: 99%
“…10.3389/feart.2024.1286229 topographic highs to areas of lower gradient, where they can cover hundreds or thousands of square kilometers; therefore, they are important to act as seals in hydrocarbon exploration (Armitage et al, 2009;Omeru, 2014). However, small MTCs can also occur within large channels or canyons (Sun et al, 2011).…”
mentioning
confidence: 99%